Boyzie Cekwana the South African dancing body in transition - Pienaar, Samantha (Rhodes University, Faculty of Humanities, Department of Drama, 1996)
Boyzie Cekwana is one of many black male dancers and choreographers that is currently receiving widespread support and recognition for his contribution to the field of contemporary dance in South Africa. Why certain images of the dancing body - as presented by this individual dance practitioner - are currently being promoted as artistically more viable than others by dance critics and the media is the central concern of this thesis. An analysis of the dancing body in contemporary South Africa must take into account the current post-apartheid condition, a condition of transformation and reconstruction that allows people greater freedom to select the country's leaders, popularize its heroes and heroines, market and capitalize on images and icons of a New South Africa. By opting to look specifically at a black male dancer, social appreciations of the body in terms of ethnicity and gender can be challenged. This latter area of research - the role of gender in the production, presentation and appreciation of the dancing body - is largely unchallenged in South Africa. Yet, if South African's want to truly rid themselves of the shackles of hegemonic rule, gender-construction is an area of social experience that needs intensive confrontation. Chapter one will suggest some of the obstacles that might limit the South African dance researcher seeking an indepth analysis of the black dancing body, taking into consideration the country's history of elitist and autonomous rule. Attention will be drawn to multidisciplinary sites of information that might assist the researcher in such an excavation. The context of the research, however, is less interested in historical descriptions of the dancing body than with current motivating factors behind the preferential promotion of certain images over others in contemporary dance. Personal interviews and observations will therefore also provide crucial resource material. In chapter two, a case study of Boyzie Cekwana will be made looking at his personal background and the way in which it may have informed his contemporary experiences as a black male dancer and choreographer. The underlying belief of such a case-study approach is that "it carries implications about the extents to which the resulting analysis is applicable to other similar cases" Â¹. This individual analysis includes information gathered from persona1 interviews with Cekwana; the author's own observations and experiences of Cekwana' s work at the Vita FNB Dance Umbrella, the Grahamstown National Arts Festival, and the Durban Playhouse Theatre; and analyses of articles on Cekwana by journalists, and performance reviews by dance and theatre critics such as Adrienne Sichel (The Star Tonight!), Tommy Ballantyne (The Natal Sunday Tribune) and David Coleman (The Mercury). Further examinations in chapter three and four will assess to what degree Cekwana re-presents culture-specific images of gender-modelling in his own performing body and the bodies of his multi-racial and multi-gendered dancers in selected dances. To prevent placing sole responsibility at Cekwana' s feet for the representation of the dancing body to a society in transformation, the role of dance critics and mass mediators in this process of artistic communication will also be dealt with. It is hoped that the ensuing discussion will suggest the possible effects that present frameworks of aesthetic appreciation may hold for choreographers and dancers in the country's future cultural development; this involves confronting a still controversial issue in South Africa the relationship between dance and politics, choreographer and social responsibility. The thesis will round-off very briefly with suggestions to dance practitioners and educators in South Africa of alternative ways of perceiving and appreciating the dancing body based on gender, andÂ· not just racial, constructions; this is especially invaluable in the light of current efforts to include dance as a core-curriculum subject in all schools.
Keywords: Cekwana, Ntsikelelo; Dance -- South Africa